Creating Shared Value Utilization of FABA PLTU Pacitan - Raden Sultani Indragunawan; Risky Tri Listirta; Moh. Bangkit Ramadhan (Prospect Publishing, 2023)
As Fly Ash & Bottom Ash (FABA) producer, Pacitan Generating Unit, which is one of PLN Nusantara Power's units located in the southern part between East Java and Central Java, has an obligation to manage FABA. As waste, FABA, which originally had the status of Hazardous & Toxic Waste (B3) until it became Non-hazardous waste, must be managed properly following Government Regulations and Minister of Environment & Forestry Regulations. FABA management carried out by UP Pacitan is in the form of massive utilization of FABA in the packaging of the Corporate Social Responsibility (CSR) program or what is currently also known as Social & Environmental Responsibility. FABA utilization program is in line with the corporate strategy in maintaining the life of the landfill as FABA storage area which will continue to be filled as long as the PLTU Pacitan operates. In addition, this program also have positive impacts on the wider community by transforming FABA into village road casting activities, construction of habitable houses, stabilization of non-productive land, revitalization of rest areas in Ring I, and FABA is used as a mixture of paving/brick production by micro, small and medium enterprises. The creation of